Les décisions pénales dans les causes d’homicide au tribunal de Montréal, de 1985 à 1989 - Noël-Grandmaison, Rachel (Criminologie, 1996)
This paper tries to shed a light on the attrition process and on the factors influencing the sentencing's decision making process, for criminal homicide cases prosecuted in Montreal between 1985 and 1989 inclusively. The results showed that unlike the police mainly laying murder charges, 55 % of the 142 sentenced were found guilty of manslaughter. Therefore a large number has less than eight years in prison to serve before eligibility to full parole. The accused who commited an homicide associated with another crime or a settling of accounts, who went through a trial, who had a criminal record and who killed a woman significantly encounter a greater possibility to be sentenced on a murder charge. Yet a sequence in the decision making process can be observed: once is settled the type of charge to be definitive at the end of the criminal process, the factors studied influence rather little the severity of the imposed sentence. Finally the author points out how the prosecution mode of these homicide cases played an important part on the two levels of decision.